Motivation and identity: A psychoanalytic perspective on the turn to identity in motivation research. (May 2017) - Driver, Michaela
Taking the recent turn to identity in motivation research as its starting point, the study attempts to move the field further beyond instrumentalizing and fractionalizing conceptions in which motivation is simply a question of pulling the right levers. Drawing on a psychoanalytic, particularly Lacanian, perspective and an analysis of 51 narratives shared by employees from a number of occupations, it develops a more fine-grained and complex understanding of how motivation functions in the context of identity work. Specifically, the study explores how motivation is invariably mapped onto internal struggles with unconscious subjectivity and desire. These may align individuals more with organizational ideals of the properly motivated employee, but also create an empowering space in which employees can work through work-related fantasies and find enjoyment on their own terms. The implications of this perspective are discussed.